Low-dose GnRH antagonist protocol is as effective as the long GnRH agonist protocol in unselected patients undergoing in vitro fertilization and embryo transfer - Shang-Yu Huang; Hong-Yuan Huang; Hsing-Tse Yu; Hsin-Shin Wang; Chun-Kai Chen; Chyi-Long Lee; Yung-Kuei Soong (Elsevier, 2011)
Objective: The present retrospective and controlled comparative study was designed to evaluate the pregnancy rate achieved using a modified, fixed, multiple-dose 0.125 mg gonadotropin-releasing hormone (GnRH) antagonist protocol with the long GnRH agonist protocol as the control group. Materials and methods: One hundred and twenty unselected women between 30 and 40 years of age, in their first cycle of IVF/ICSI, with a baseline follicle-stimulating hormone (FSH) <10 IU and an antral follicle count >3 were assigned into two groups: (1) the study group received 0.125 mg of cetrorelix daily starting on Day 6 of stimulation; and (2) the control group received leuprolide daily starting in the mid-luteal phase of the preceding cycle. Both groups were given a flexible dose of recombinant FSH for stimulation. An ongoing pregnancy rate of more than 12 weeks was the primary outcome measure of the study. Results: Primary and secondary outcomes were comparable in both groups. A shorter duration of stimulation, a lower dosage of recombinant FSH consumption and a thinner endometrium on the day of human chorionic gonadotropin administration were all observed in the GnRH antagonist group. Conclusion: A dosage of 0.125 mg GnRH antagonist protocol was effective for these unselected patients during IVF/ET.